A Naturalistic Behavioral Intervention to Increase Interaction between Siblings with and without Autism. Issue 6 (November 2021) - Watkins, Laci; Tomeny, Theodore; O'Reilly, Mark; Sillis, Katherine H.; Zamora, Claudia
Research suggests that including typically developing siblings in interventions for children with autism spectrum disorder (ASD) may be beneficial. However, studies have predominantly involved only participants with mild symptoms of ASD and have not also reported outcomes for the typically developing sibling. The purpose of this study was to address these gaps by replicating and extending an intervention package consisting of structured, interest-based play activities, adult instruction and modeling, and response to child questions. A reversal design across two sibling dyads was used to demonstrate the effects of the intervention on the social interaction behaviors of the child with ASD and typically developing sibling. Social interaction increased for both sibling dyads, results generalized for one dyad, and multiple measures indicated a high level of social validity. Recommendations for practitioners and caregivers working with children with ASD and potential areas of future research are discussed.